2021
DOI: 10.1002/star.202100021
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Antibacterial Activity of Encapsulated Rosemary Essential Oil within Amylose Nanostructures as a Natural Antimicrobial in Food Applications

Abstract: Rosemary essential oil (REO) is a natural phenolic compound with high antimicrobial activity. However, its application is limited due to the poor solubility in water, instability, and high volatility. In this study, REO is incorporated into the high amylose corn starch (HACS) nanostructures by inclusion complexation. The characterization of the obtained nanostructures is done by SEM, TGA, FTIR, and XRD. Encapsulation efficiency, loading capacity, stability, release, and antibacterial activity of encapsulated R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The solution (3 mL) was pulled out and replaced by fresh 50% ethanol. The sampling continued for the next 24 h [ 27 ]. The released curcumin from the film samples was assessed at 425 nm using a spectrophotometer (JASCO, Tokyo, Japan) [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The solution (3 mL) was pulled out and replaced by fresh 50% ethanol. The sampling continued for the next 24 h [ 27 ]. The released curcumin from the film samples was assessed at 425 nm using a spectrophotometer (JASCO, Tokyo, Japan) [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is observed considering that the minimum bactericidal concentration (MBC) was higher than that of the others for L. monocytogenes (7.05 against 3.52 mg/ml) when free REO was employed. However, when it was encapsulated, the MBC not only was the same for all the bacteria tested but also decreased down to 2.5 mg/ml in all the cases (Amani et al, 2021). Advantages of encapsulation were proven in Liu et al (2021); antimicrobial activity of Mānuka EO (MEO) was improved encapsulating it into yeast cells by reducing three times the bacterial population during the same time (1 hour).…”
Section: Natural Antimicrobial Compoundsmentioning
confidence: 99%
“…On the other hand, rosemary can reduce the risks associated with foodborne infections and intoxications due to its bacterial growth inhibition, biofilm formation inhibition, and food shelf‐life prolongation, which thus strongly indicate that rosemary extracts and secondary metabolites will play an important role and show promising potential in food packaging (Lencova et al., 2022). REO can be incorporated into the high amylose corn starch nanostructures, and this complex significantly promotes the thermal stability of REO as well as its solubility and antibacterial activity (Amani et al., 2021). In addition, it has also been found that the incorporation of REO with zinc oxide nanoparticles significantly promoted the mechanical properties, barrier properties, moisture resistance, and antibacterial activity of sodium caseinate films (Alizadeh‐Sani et al., 2021).…”
Section: Rosemary As a Functional Food Ingredient In The Food Science...mentioning
confidence: 99%